The Effect of Atmosperical Aridity on the Changes of Quantitative Parameters of Horticultural and Arable Crops - Lakatos, László; Karácsony, Zoltán; Racskó, József; Zhong-Fu, Sun; Yingchun, Wang (Acta Agraria Debreceniensis, 2005)
The occurence of atmospherical drought causes serious water-supply problems in the most cases of our domestic agricultural plant species. This paper was studied, how can we quantificate the atmospherical drought, with the help of a low input (relative humidityof the air, temperature) index. If this index (LSZI) characterized the atmospherical drought well, it will suitable to estimate the yield amount of agricultural plants.The index elaborated by the authors was tested on county average crop yield of 14 agricultural plant species. Moreover we compared the atmospherical drought index (LSZI) to other aridity parameters, how suitable for estimate the yield amount.Result of experiments show that, the atmospherical drought index (LSZI) can be used well by several agricultural plant species in especially coern and sugar-beet to estimate yield amount. Excellent results were found by comparison to other aridity indexes, this means it is worth using in the aridity researches in the future.